HUMOR VERBAL DALAM ROASTING TIGA “CAPRES” PADA ACARA LAPOR PAK! : ANALISIS GTVH - Sukma Sukma; Mulyadi Mulyadi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2026)
This study aims to analyze verbal roasting humor in the show Roasting Tiga “Capres” on the program Lapor Pak! using a semantic humor approach with the General Theory of Verbal Humor (GTVH) by Attardo and Raskin. This research is significant because verbal roasting humor in political contexts has not been systematically analyzed from a linguistic perspective, and thus this study can reveal how language strategies and humor structures are employed to convey criticism, negotiate power, and influence public perception. This study is qualitative with a descriptive method, using observation and note-taking techniques, and data analysis following the Miles and Huberman procedures. The results show that 31 instances of verbal roasting humor were identified and analyzed using six Knowledge Resources (KRs), namely: SO (personal identity, competence, public image, power relations), LM (faulty analogy, belittling, figurative language, inversion, comparison), SI (situational context, including participants, activities, objects, and conditions that form the humor), TA (humor target centered on a specific figure), NS (dominance of dialogue form), and LA (word arrangement consistently using set-up and punch line to create humor). This study enriches the study of language by examining the strategies, structures, and functions of verbal humor in political interactions, while also providing new insights for the analysis of political communication.